World Russian People’s Council and Interreligious Council of Russia: New Formats of Interreligious and Interethnic Dialogue in Post-Soviet Russia at Turn of 20th — 21st Centuries - Yu. Yu. Ierusalimskiy; A. B. Rudakov (Научный диалог)
The article is devoted to the study of the role of the World Russian People’s Council and the Interreligious Council of Russia in establishing interfaith dialogue in post-Soviet Russia. The speeches of delegates at council meetings and sessions of the World Russian People’s Council are analyzed. The importance of interfaith dialogue at the site of the World Russian People’s Council was confirmed by the participation of the highest clergy and clergy of different confessions of the Russian Federation and the Commonwealth of Independent States at the cathedral meeting “Russia: the path to salvation” (1998). The importance of the agreement on the establishment of the Interreligious Council of Russia (1998) for the representation in it of the “traditional religions” of the Russian Federation: Orthodoxy, Islam, Buddhism and Judaism is noted. The assessments of publicists and researchers in relation to the Interreligious Council of Russia, including critical ones, are given. It is noted that the interaction of the Russian Orthodox Church with representatives of other confessions continued at the 5th and 6th World Russian People’s Councils in 1999 and 2001. The conclusions indicate that the activities of the World Russian People’s Council and the Interreligious Council of Russia at the turn of the XX—XXI centuries showed the importance of cooperation and respectful relations between representatives of Orthodoxy, Islam, Buddhism, Judaism and other confessions.